Dynamic testing to determine and predict trampoline function - Brown, O. H.; Mullineaux, D. R.; Mulloy, F. (Sports Engineering, 2021)
Safety standards for domestic trampolines are based on static-load testing using a factor of five times the maximum intended user mass. This paper presents a dynamic test method for trampolines, and provides measures of the users` performance (e.g., peak acceleration, Accmax) and injury risk (e.g., mean rate of change of acceleration, Jerkmean). Uniform masses (41-116 kg) were dropped from 0.66 m onto the bed centre of nineteen different trampolines. Trampoline bed and spring stretches, mass flight time (FlightT) and accelerations were recorded using motion capture and accelerometers. Thirty-seven percent of trampolines exceeded the static safety standard bed deformation limits (80% of frame height) by 11 ± 6% with dynamic testing (mean ± standard deviation). Across all trampolines and masses dropped, the Accmax ranged from 5.1 to 7.6 g, suggesting the factor of five used in static-loading safety standards needs reviewing. Statistically significant negative correlations (p < 0.05) were found between trampoline bed diameter and Accmax (r = - 0.88), Jerkmean (r = - 0.77) and FlightT (r = - 0.82). Furthermore, significant correlations (p < 0.05) were also found between the mass dropped and Accmax (r = - 0.27), Jerkmean (r = - 0.59) and FlightT (r = 0.25). The combined effects of the spring constants, number of springs, bed diameters and masses dropped were described in predictive multivariate equations for Accmax (explained variance, R2 = 95%) and maximum vertical bed deformation (R2 = 85%). These findings from dynamic testing may assist manufacturers in designing trampolines that meet safety standards while maximising user performance and reducing injury risk.